Impregnation of ZnO onto a Vegetal Activated Carbon from Algerian Olive Waste: A Sustainable Photocatalyst for Degradation of Ethyl Violet Dye - Ala Abdessemed; Shivatharsiny Rasalingam; Sanna Abdessemed; Kamel El Zin Djebbar; Ranjit Koodali (International Journal of Photoenergy)
This study is aimed at developing a simple and low-cost method to fabricate ZnO-loaded porous activated carbon (AC-ZnO) prepared from the Algerian olive-waste cakes and utilize it as a photocatalyst for the degradation of Ethyl Violet dye. The synthesized AC-ZnO material was characterized using powder X-ray diffraction, BET surface area measurements, Raman microscopy, thermogravimetric analysis, UV-visible diffuse reflectance spectroscopy, and zeta potential measurements. The degradation efficiency was evaluated with Ethyl Violet (EV) dye in aqueous solution under UV irradiation supplied by a Xenon arc lamp through a Pyrex glass filter (cutoff 280 nm), and the degraded products were identified by using electrospray ionization mass spectroscopy. Additional experiments were carried out under N2 flow and with isopropyl alcohol to examine the role of superoxide and hydroxyl radicals, respectively. The amount of ●OH radical formed on irradiated AC-ZnO was tested with terephthalic acid which can act as a chemical trap for the ●OH radicals. The results from this study indicate that the AC-ZnO is a potential catalyst for the pollutant removal and the ●OH radicals are the key species for the degradation of EV. Further, this study opens up an opportunity to produce cheaper activated carbon support from olive wastes for environmental remediation applications.